Enhanced Reaction Kinetics in Sodium‐Ion Batteries Achieved by 3D Heterostructure CoS2/CoS with Self‐Induced Internal Electric Field - Jin Liang; Jiawen Sun; Xin Cao; Xiaoshan Li; Xiaoyi Chen; Ruizhe Xing; Jie Kong (Advanced Science)
Abstract The sluggish charging and restricted mass transfer of cobalt‐based sulfides have provoked in cycling stability, poor rate, and low initial coulombic efficiency, impeding their practical application. Developing electronic configurations and heterostructures are effective methods to improve conductivity and accelerate mass transfer. In this work, heterostructured carbon/cobalt sulfides embedded in honeycomb‐like nitrogen‐doped carbon (HC@CoS2/CoS/NC) were proposed as a cost‐effective strategy. These composites feature interconnected channels, facilitating rapid electron transport and efficient electrolyte diffusion. This self‐induced internal electric field design of HC@CoS₂/CoS/NC enhanced the charge movement, inherent conductivity and optimized the electrochemical kinetics as anode materials. Theoretical calculations indicate that the development of heterostructures with self‐induced internal electric fields is crucial for improving the charge particle/electron movement during the charge–discharge cycles of sodium‐ion batteries (SIBs), leading to enhanced Na+ diffusion. This anode demonstrated a high specific capacity of 809.0 mAh g−1 at 0.1 A g−1, retaining a capacity of 465.2 mAh g−1 after 700 cycles at 15 A g−1. When paired with Na3V2(PO4)3, the full‐cell maintained a specific capacity of 108.9 mAh g−1 after 200 cycles at 1.0 A g−1. This research presents an effective approach for developing transitional metal sulfide heterostructures as high‐performance anode materials for SIBs.